Priorities for a development-friendly EU Carbon Border Adjustment (CBAM) - Clara Brandi (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
The European Commission unveiled the Carbon Border Adjustment Mechanism (CBAM) in July 2021 as part of its "Fit for 55" climate-policy package. The European Commission had announced this trade-policy instrument under the Green Deal in 2019 as a means of implementing more ambitious climate-policy goals without energy-intensive sectors transferring their emissions abroad (carbon leakage). The CBAM proposal envisages imposing a levy on imports in certain energy-intensive European sectors that is proportional to the carbon content of the goods concerned. The proposal complements the EU's existing Emissions Trading System by requiring importers of goods purchased from especially energy-intensive sectors (steel, cement, electricity, fertiliser and aluminium) abroad to purchase carbon certificates based on emissions data from abroad. CBAM is primarily designed to promote an ambitious climate policy for the EU. However, the EU's current proposal creates the impression that it is mainly about improving domestic competitiveness at the expense of climate-policy effectiveness and development prospects.The draft legislation must now be fleshed out in detail by the EU member states and the European Parliament. In addition to addressing climate-policy effectiveness and compatibility with WTO legislation, account must also be taken of the impact on European trading partners, and, in particular, poor developing countries. Many developing countries are expected to face additional export costs as a result of the CBAM. The EU should carefully evaluate the associated disadvantages for developing countries and work towards achieving a development-friendly design of the mechanism. Corresponding improvements should be made to the CBAM in the EU's legislative process going forward: The EU must ensure that the border adjustments do not have a detrimental impact on poor countries. Least developed countries (LDCs) should be exempted from the CBAM. The EU should provide targeted support to the developing countries affected by the mechanism, for instance, by building their capacity for implementing the CBAM and for reducing carbon emissions in the sectors concerned. The EU should assist low- and middle-income partner countries with the decarbonisation of their manufacturing industries. The EU should also recycle revenue from the CBAM by deploying it primarily for climate-policy purposes abroad. The affected countries should be involved to a greater extent in future through consultations and diplomatic dialogue in the process for further developing the mechanism.
Keywords: 330